The application of plastic with mixed spent coffee grounds for LED lamp: การประยุกต์พลาสติกผสมกากกาแฟสำหรับโคมไฟแบบหลอดแอลอีดี - ดีแจ้ง, นุชจิรา (Rattanakosin Journal of Science and Technology, 2021)
The plastic composite with spent coffee ground addition 1, 2, 3, 4 and 5 g per Polyethylene 20 g, there were mixed with hot plate temperature 100 oC It formed to shape by plastic plate mold with varying thickness 1, 2 and 3 mm. The result of addition spent coffee ground, the plastic composites were presented the decreased density, opaque characteristic and trended to dark brown color. The effect of transparent resistance of plastic composite plastic improved the adsorb the light incident that corresponded with increasing thermal conductivity. The plastic composite was good conducted the heat flow from the leading light source. It affected the bended structure of plastic under loading force. The conclusion that it was clearly dominated the thermal property in plastic composite by the spent coffee ground content.